Identification of a novel fluoropyrrole derivative as a potassium-competitive acid blocker with long duration of action. Issue 13 (1st July 2017) - Nishida, Haruyuki; Arikawa, Yasuyoshi; Hirase, Keizo; Imaeda, Toshihiro; Inatomi, Nobuhiro; Hori, Yasunobu; Matsukawa, Jun; Fujioka, Yasushi; Hamada, Teruki; Iida, Motoo; Nishitani, Mitsuyoshi; Imanishi, Akio; et al.
Graphical abstract: Abstract: With the aim to find a novel long-lasting potassium-competitive acid blocker (P-CAB) that would perfectly overcome the limitations of proton pump inhibitors (PPIs), we tried various approaches based on pyrrole derivative1b as a lead compound. As part of a comprehensive approach to identification of a new drug, we explored excellent compounds that have low lipophilicity by introducing a polar hetero-aromatic group at position 5 of the pyrrole ring. Among the compounds synthesized, fluoropyrrole derivative37c, which has a 2-F-3-Py group at the fifth position, lower pKa, and much lower C log P and log D values than1b dose, showed potent gastric-acid suppressive action resulting from gastric H +, K + -ATPase inhibition in animal models. Its maximum intragastric pH elevation effect was strong in rats, and its duration of action was much longer than that of either lansoprazole or lead compound1b in dogs. Therefore, compound37c can be considered a promising new P-CAB with long duration of action.